Narrativas docentes e experiência vivida: uma reflexão das concepções de ser humano e sobre o ser professor de filosofia - Silva, Luís Carlos da (Universidade Federal de São Carlos, 2025)
This thesis aims to investigate the conceptions of the human being expressed by Philosophy teachers working in public high schools in the state of São Paulo, Sorocaba, Brazil . Based on the premise that an educator’s understanding of the human being directly influences their teaching practice and educational vision, the research sought to comprehend how these conceptions manifest in everyday school life and what contributions they offer toward a more humanizing education. Ten teachers from different schools across the state were interviewed to capture their philosophical, pedagogical, and existential perceptions about human nature, its potentialities, and challenges in the contemporary context. The theoretical framework is primarily grounded in the philosophical anthropology of Max Scheler and the existential personalism of Viktor Frankl, in addition to contributions from other classical and modern thinkers such as Plato, Marx, Descartes, Heraclitus, Hegel, and Aristotle, among others. The research integrates these references with the teachers' narratives, demonstrating how different philosophical traditions still influence contemporary pedagogical thinking. The methodological approach was qualitative, with a phenomenological and constructivist emphasis, aiming to understand the teachers' experiences based on their concrete realities, educational paths, and theoretical foundations. The analysis values the teachers’ narratives as legitimate sources of knowledge production about the human being and the role of Philosophy in schools. The findings reveal a plurality of conceptions of the human being among the interviewed teachers, reflecting influences from a wide range of philosophical perspectives — from Cartesian rationalism to Heraclitean becoming, from historical materialism to existentialist transcendence. Despite the challenges faced in their school contexts — such as the devaluation of Philosophy, limited class hours, and a rigid curriculum structure — these teachers demonstrate a strong commitment to the ethical, critical, and reflective formation of their students. Their testimonies reflect an active resistance to the dehumanization imposed by contemporary social, political, and educational crises, reaffirming Philosophy as a fundamental tool for fostering awareness, empathy, and human dignity. The research concludes that the teaching of Philosophy, when grounded in a conception of the human being attentive to historicity, freedom, culture, and spirituality, has the potential to contribute to an emancipatory education and the construction of a more just, supportive, and humanized society. This study thus hopes to provide theoretical and practical support for strengthening the role of Philosophy in basic education and for recognizing the Philosophy teacher as a key agent of social transformation and a builder of consciousness.
Teacher narratives and lived experence: a reflection on conceptions of being human and on being a philosophy teacher
Keywords: Filosofia; Concepção de ser humano; Professores; Educação; Philosophy; Conception of the human being; Teachers; Education; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 8. Trabalho Decente e Crescimento Econômico; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes